Superior mesenteric artery-related outcomes in fenestrated/branched endografting for complex aortic aneurysms - Gallitto, E.; Faggioli, G.; Vacirca, A.; Lodato, M.; Cappiello, A.; Logiacco, A.; Feroldi, F.; Pini, R.; Gargiulo, M. (Frontiers in Cardiovascular Medicine, 2023)
AIM. Early/follow-up durability of superior mesenteric artery (SMA) stent-grafts is crucial after fenestrated/branched endografting (FB-EVAR) in complex (CAAAs) and thoracoabdominal aortic aneurysms (TAAAs). Aim of the study was to report early/midterm outcomes of SMA incorporated during FB-EVAR procedures. METHODS. FB-EVAR performed between 2016 to 2021 were reviewed. Anatomical SMA characteristic were analyzed. SMA configuration was classified in 3 types according to the angle between SMA main trunk and the aorta: A-perpendicular, B-downward, C-upward. SMA-related technical success (SMA-TS: cannulation and stenting, patency at completion angiography without endoleak, stenosis/kinking, dissection, bleeding and 24-hour mortality) and SMA-adverse events (SMA-AE: one among bowel ischemia, stenosis, occlusion, endoleak, reinterventions or SMA-related mortality) were assessed. RESULTS. Two-hundred FB-EVAR procedures with SMA as target artery were performed. SMA configuration was A, B and C in 132(66%), 63(31%) and 5(3%) cases, respectively. SMA was incorporated with fenestrations and branches in 131(66%) and 69(34%) cases, respectively. Directional branch (P<.001), aortic diameter >35mm at the SMA level (P<.001) and >2 SMA bridging stent-grafts (P=.001) were more frequent in TAAAs. Relining of the SMA stent-graft with bare metal stent was necessary in 41(21%) cases to correct an acute angle between stent-graft and native artery (39), stent-graft stenosis (1), or SMA dissection (1). Relining was associated with type A or C SMA configuration (OR:17;95%CI:1.8-157.3;P=.01). SMA-TS was achieved in all cases. Overall, 15(7.5%) patients had SMA-AE [early:9(60%), follow-up:6(40%)] due to stenosis (2), endoleak (8) and bowel ischemia (5). Aortic diameter >35mm at the SMA level was an independent risk-factor for SMA-AE (OR:4;95%CI:1.4-13.8;P=.01). Fourteen (7%) patients died during the hospitalization with 10(5%) events within 30-postoperative day. Urgent cases (OR:33;95%CI:5.7-191.3;P=.001), peripheral arterial occlusive disease (OR:14;95%CI:2.3-88.8;P=.004) and bowel ischemia (OR:41;95%CI1.9-87.9;P=.01) were risk-factors for 30-day/in-hospital mortality. The mean follow-up was 32+24 months; estimated 3-year survival was 81%, with no case of late SMA-related mortality or occlusion. Estimated 3-year freedom from overall and SMA-related reinterventions was 74% and 95%, respectively. CONCLUSION. SMA orientation determines the necessity of stent-graft relining. Aortic diameter >35mm at the SMA level is predictor of SMA-AE. SMA-related outcomes of FB-EVAR are satisfactory with excellent technical success and promising clinical outcomes during follow-up.